AB0063 AGING CARTILAGE IN WILD-TYPE MICE: AN OBSERVATIONAL STUDY. (2nd June 2020) - Akoum, J.; Tahiri, K.; Etienne, F.; Corvol, M. T.; Rannou, F.; Nguyen, C.
Abstract : Background: Many animal models of osteoarthritis (OA) have been used to study the pathogenesis of cartilage degeneration 1 . In mice, spontaneous OA can occur in wild-type or genetically modified animals. The first report of spontaneous OA developing in wild-type mice was published in 1956 2 and changes affecting the knee joint were further related to OA by using ultrastructural- histochemical analyses. However, a quantitative assessment of age-related evolution of OA-type cartilage lesions is lacking. The OA Research Society International (OARSI) grading score was adapted to semi-quantify histopathogical changes occurring in OA animal models, including mice 3 . The OARSI score has been used to describe changes occurring in induced or genetic OA mouse models but not to describe spontaneous age-related evolution of OA-type cartilage lesions in wild-type mice. Objectives: We aimed t o describe the spontaneous evolution of age-related changes affecting knee joint articular cartilage, walking speed and a serum biomarker of cartilage remodeling in C57BL/6 wild-type male mice. Methods: Histological changes were assessed by the OARSI score in newborn, 1-week- and 1-, 3-, 6-, 9- and 12-month-old C57BL/6 wild-type male mice, walking speed by the Locotronic system, and serum C-terminal telopeptide of type II collagen (CTX-II) content by ELISA in 1-, 3-, 6-, and 9-month-old C57BL/6 wild-type male mice. Results: Mean (SD) OARSI score increased from 0.2(0.3) to 1.3(0.6) (p=0.03) between 1 and 3 months of age and from 1.3(0.6) to 3.3(0.6) (p=0.04) between 3 and 6 months of age. Mean walking speed was stable between 1 and 6 months of age but decreased from 11.4(1.8) to 3.2(0.8) cm.s-1 (p=0.03) between 6 and 9 months of age. Serum CTX-II content was maximal at 1 month of age, then decreased from 12.2(8.5) to 2.4(8.4) pg/ml (p=0.02) between 1 and 3 months of age, remaining low and stable thereafter. Conclusion: C57BL/6 wild-type male mice showed continuously increasing osteoarthritic changes but delayed decreasing walking speed with age. These variations were maximal between 3 and 9 months of age. Maximal serum CTX-II content preceded these changes. References: [1]McCoy AM. Animal Models of Osteoarthritis: Comparisons and Key Considerations. Vet Pathol. 2015;52(5):803-18. [2]Sokoloff L. Natural history of degenerative joint disease in small laboratory animals.I. Pathological anatomy of degenerative joint disease in mice. AMA Arch Pathol.1956;62(2):118-28. [3]Glasson SS. The OARSI histopathology initiative - recommendations for histological assessments of osteoarthritis in the mouse. Osteoarthritis Cartilage. 2010;18 Suppl 3:S17-23. Disclosure of Interests: Joulnar Akoum: None declared, Khadija Tahiri: None declared, François Etienne: None declared, Marie-Thérèse Corvol: None declared, François Rannou Grant/research support from: Pierre Fabre, Fidia, MSD, Pfizer, Bone Therapeutics, Expanscience, Grunenthal, Thuasne, Genévrier, Fondation Arthritis, Consultant of: Pierre Fabre, Fidia, MSD, Pfizer, Bone Therapeutics, Expanscience, Grunenthal, Thuasne, Genévrier, Speakers bureau: Pierre Fabre, Fidia, MSD, Pfizer, Bone Therapeutics, Expanscience, Grunenthal, Thuasne, Christelle Nguyen: None declared